On generalizations of Soft Fuzzy GÎ´ Semi-Closed Sets - Visalakshi, V.; Vidhya, D.; Yogalakshmi, T. (International Journal of Engineering and Technology, 2018)
In this paper, soft fuzzy GÎ´ semi closed set is introduced. Using soft fuzzy GÎ´ semi closed set, generalized soft fuzzy GÎ´ semi-continuous function, generalized soft fuzzy GÎ´Â Â semi-connected space, generalizedÂ soft fuzzy FÏƒ semi-compact space are introduced and studied. In this connection, properties and characterizations are established. Also soft fuzzy T-FÏƒ space is introduced and studied. Examples and counter examples are provided wherever necessary.Â Â